Testing Efficiency of Sudan’s IslamicBanks for Funding Socio-Economics Development using World Rankings Indices - Omer Allagabo Omer Mustafa (Jurnal Internasional Ekonomi Islam, 2022)
Islamic banks(IBs) are based on Sharia principles, which call for attention to human development. Islamic modes of finance (Murabaha, Musharaka, …etc.) enables IBs to achieve socio-economic development through financing real projects compared to the conventional ones based on interest lending. The study aims to measure the efficiency of Sudan’s IBs in financing socio-economic development using world rankings indices(WRsIs). The methodology took banking finance as an independent variable while socio-economic development was the dependent variable. Socio-development was measured by WRsIs including human development, press freedom, political rights, civil liberties, and prosperity. Economic development was measured by GDP growth and GDP per capita. Data covering (2011-2021) was collected from the Central Bank of Sudan (CBOS) and World Economic databases. The ordinary least squares method was used to estimate the nexus between variables. The results concluded that except for political rights, the rapid growth of banking finance (11% in 2011 to 43% in 2021) does not significantly positively influence socio-economic development. Because more50% of finance was provided through Murabaha (high return and low risk) but it doesn’t stimulate economic development. The study recommends the CBOS revise policies and practical frameworks of IBs to enhance social dimensions as well as WRsIs.